Real world use of hybrid‐closed loop in children and young people with type 1 diabetes mellitus—a National Health Service pilot initiative in England. Issue 2 (4th December 2022) - Ng, Sze May; Wright, Neil P.; Yardley, Diana; Campbell, Fiona; Randell, Tabitha; Trevelyan, Nicola; Ghatak, Atrayee; Hindmarsh, Peter C.
Abstract: Aims: Hybrid closed‐loop (HCL) systems are characterised by integrating continuous glucose monitoring (CGM) with insulin pumps that automate insulin delivery via specific algorithms and user‐initiated insulin delivery. The aim of the study was to evaluate effectiveness of HCLs on HbA1c, time‐in‐range (TIR), hypoglycaemia frequency and quality of life measures in children and young people (CYP) with T1D, and their carers. Methods: Patients were recruited prospectively into the National Health Service (NHS) England real‐world HCL observational study from the 1st of August 2021 to the 10th of December 2022 from eight paediatric diabetes centres in England. Results: There were 251 CYP (147 males, 58%) with T1DM recruited with a mean age at recruitment of 12.3 ( SD 3.5) (range 2–19) years. Eighty nine per cent of the CYP were of white ethnicity, 3% Asian, 4% black and 3% mixed ethnicity, and 1% were recorded as others. The HCL systems used in the study were: (1) Tandem Control‐IQ AP system, which uses the Tandem t:slim X2 insulin pump (Tandem Diabetes Care, San Diego, CA) with the Dexcom G6® CGM (Dexcom, San Diego, CA) sensor; (2) Medtronic MiniMed™ 780G (Medtronic, Northridge, CA) and (3) CamAPS FX (CamDiab, Cambridge, UK.) All systems were fully funded by the national health service. Conclusions: The results of the NHS England Closed Loop Study in Children and Young People showed improvements in glycaemic control, TIR, frequency of hypoglycaemia, hypoglycaemia fear and quality of sleep for children and young people when using HCL for 6 months. Hypoglycaemia fear and quality of sleep were also improved for their parents and carers at 6 months.